Penerapan Model Pembelajaran SAVI (Somatic, Auditory, Visual, Intellectual) Untuk Meningkatkan Literasi Sains Di Kelas Tinggi - Susilawati Agustiani; Dyah Lyesmaya; Astri Sutisnawati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
The Purpose of this research were to increase of student’s science literacy by applying the model of SAVI learning (Somatic, Auditory, Visual, Intellectual) on change in object. The subject of this research is students of grade V-B SDN 1 Cikembar which amounted to 31 students. This research uses a Class Action Research methode (PTK) with four components Kemmis and Taggart’s model that was conducted in two cycles. The instrument for collected data in this research are activities of teacher, data in this research are activities of students, and questionnaire of student’s science litercy. The apply model of SAVI can increase of teacher activities with the average values obtained in the first cycle is 76% and second cycle is 87%. Increase of student learning activities with the average values obtained in the first cycle of 71% and second cycle is 83%. Increase of student’s science litercy with the average values obtained in the first cycle is 75% and second cycle is 86%. The apply model of SAVI also can increase the thoroughness of learning outcomes IPA. The percentage of students who complete the first cycle is 61% and second cycle is 94% and there was an increase in the average N-Gain score of 0,67 with the medium category.